Assessment of Factors Causing Construction Delays in Building Construction Projects in Somaliland - Abdisalam Yusuf Duale; Werku Koshe Hareru; Tewodros Ghebrab; Solomon Mulugeta; Tewodros Gedefaye (Advances in Civil Engineering)
Construction delays (CDs) pose persistent challenges in building projects, leading to budget and schedule overruns. This study aimed to investigate the root causes of CD in Somaliland, and ranks the factors based on significance. A cross-sectional study design was employed to collect quantitative data through questionnaires and qualitative insights through interviews with key industry stakeholders. In total, 95 delay factors were considered and 41 were selected through preliminary screening. Among the 41 tested factors the critical top 10 factors were identified. It is found that poor construction site management is the first significant cause of delay in projects (relative importance index, RII = 0.863). The escalation of material prices secured the second position (RII = 0.834). The lack of capable consultants takes the third rank (RII = 0.833). Poor resource management by contractors and low labor productivity, inadequate early planning, take the fourth, fifth, and sixth ranks, respectively. Interview findings agree with these results, highlighting poor construction management practices, delay in payments, poor cash-flow managements, inadequate project planning, and material price escalation, lack of capable consultants, weather conditions, and inaccurate project estimations. In conclusion, poor site management, escalation of materials price, lack of capable consultants, low productivity of labor, lack of supervision, inadequate early planning of the project, delay in payment, and poor cash-flow management are critical factors requiring attention to improve timely completion. Therefore, the stakeholders in Somaliland and similar contexts can proactively work on assigning the right person in the right position, develop a comprehensive project plan that includes a detailed resource allocation strategy, clearly define the scope of work for consultants, including their responsibilities, deliverables, and project milestones, and conduct regular inspections of the site to identify any potential issues or deviations from the project plan. Additionally, the project clients should ensure timely payment, and the contractors should enhance their cash-flow management.